The Implementation of Student Guidance in Karawang Islamic Middle School - Nurfadilla, Vania; Sutarjo, Sutarjo; Karyawati, Lilis (Edumaspul: Jurnal Pendidikan, 2022)
Planning for student guidance in school inclusion is carried out at the beginning of the new school year in the school work meeting agenda by conducting, identifying needs, interests, talents through assessment activities for students with special polling needs and spreading interest to students. Implementation of student guidance in schools is carried out by combining the special needs of students with the class system. In the implementation of guidance there is a positive interaction between crew members and students. But to develop leadership crew members are not involved. Guidance on school evaluation in inclusive schools is carried out with two things in mind in the evaluation, namely evaluation of program management and evaluation of school fee development. The success of school guidance in schools comes from inclusion in the form of achievement and attitude change and the development of independent schools. The purpose of this research is to describe how the process of student management management is held in inclusive school education providers. The method used in this study is a descriptive method with a qualitative approach. Data was collected by means of interviews, and observations. The results showed that the scope of student development in schools was divided into three, namely leadership guidance through OSIS, extracurricular, academic and non-academic guidance and development.